Economics of Information Security and Privacy - Moore, Tyler; Pym, David; Ioannidis, Christos (Springer US : Imprint: Springer, 2010)
The Workshop on the Economics of Information Security (WEIS) is the leading forum for interdisciplinary research and scholarship on information security and privacy, combining ideas, techniques, and expertise from the fields of economics, social science, business, law, policy, and computer science. In 2009, WEIS was held in London, at UCL, a constituent college of the University of London. Economics of Information Security and Privacy includes chapters presented at WEIS 2009, having been carefully reviewed by a program committee composed of leading researchers. Topics covered include identity theft, modeling uncertainty's effects, future directions in the economics of information security, economics of privacy, options, misaligned incentives in systems, cyber-insurance, and modeling security dynamics. Economics of Information Security and Privacy is designed for managers, policy makers, and researchers working in the related fields of economics of information security. Advanced-level students focusing on computer science, business management and economics will find this book valuable as a reference.